Gerakan Ekonomi Satyagraha Hindu Bali Melalui Labelisasi Non-Halal Sukla - Jumari Jumari (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: In Bali, the enforcement of Halal Product Guarantee which is a product of law and applicable throughout the territory of NKRI, has gained "resistance" from some Hindu Balinese people. Since 2014, they have demonstrated "resistance" by inflating the Gerakan Ekonomi Satyagraha, as an attitude of rejection of the law that they value is unfair, discriminatory and benefits only one religious community (Islam).Gerakan Ekonomi Satyagraha can be viewed from two sides, as a militant rise of militancy and as threat of seed of intolerance. At the level of life, this movement is a manifestation of the phenomenon of social conflict that is inherent in a heterogeneous society. If not properly managed will bear prejudice, discrimination, until the form of physical violence and death.Conversely, if managed properly it will give birth to peace. The role of religion against the Gerakan Ekonomi Satyagraha can be done through three ways, namely the internal mechanisms of religious communities, inter-religious mechanisms, and mechanisms at the systemic level.If social conflicts are understood as an inherent part of a heterogeneous society, then efforts to manage the positive potential of social conflict must be perpetuated.Moreover, if social conflict is seen as a source of change, then efforts to manage differences must be done continuously, and peace is not something static, silent and silent without dynamism.Keywords:Gerakan Ekonomi Satyagraha, Hindu, Bali